New methods of assessing wind erosion risk: Innovative approach to soil protection respecting windbreak effect - KUČERA, Josef; PODHRÁZSKÁ, Jana; STŘEDA, Tomáš; STŘEDOVÁ, Hana; FUKALOVÁ, Petra; PAPAJ, Vladimír; BLECHA, Martin; SZTURC, Jan (Contributions to Geophysics and Geodesy, 2024)
Research and development of new soil protection methods helps to maintain sustainable soil management and prevent the degradation of valuable agricultural resources. Wind erosion is a significant environmental issue that can severely degrade landscape, impact agricultural productivity and deteriorate air quality through increased dust emissions and atmospheric pollution. The main goal of this paper was to provide a methodological protocol for mapping and assessing wind erosion risk, taking into account protective effect of both existing and intended windbreaks. Based on the Potential Wind Erosion Risk (PWE) map, which takes into account soil and climatic conditions affecting wind erosion risk, a new map of potential wind erosion risk (RPWE) was created with the inclusion of the effect of windbreaks and their protected zones on the tolerated length of plots. Using this method, it is possible to assess wind erosion risk, model the design of new wind barriers and evaluate their effectiveness. The presented method has been developed into a web application that provides all outputs online. The assessment builds on long-term studies of wind erosion potential and methods for spatial representation of land susceptibility to wind erosion. Assessment of the current state of erosion risk with existing windbreaks as well as modelling the state when some are removed or newly planted, is fundamental when building a resilient and healthy environment. The newly developed method contributes to worldwide global land degradation prevention and offers new insights into the methodological approach for assessing wind erosion.